Ekwivalentverhoudings in tweetalige woordeboeke: Implikasies vir die databasis van 'n elektroniese tweetalige woordeboek van Suid-Afrikaanse Gebaretaal en Afrikaans - Fourie Blair, Hanelle (Lexikos, 2015)
Equivalent Relations in Bilingual Dictionaries: Implications for the Database of an Electronic Bilingual Dictionary of South African Sign Language and Afrikaans. This article is an extract from a more comprehensive theoretical framework in which a concept model for an electronic bilingual foundation phase dictionary of South African Sign Language and Afrikaans is suggested, specifically for the De la Bat School for the Deaf in Worcester, South Africa (Fourie 2013). The purpose of the proposed dictionary is to give the learners of the De la Bat School electronic access to written school word lists, with signs and examples in sign language displayed in video format — therefore in the form of an electronic dictionary. A written word list does not meet the needs of school learners in this case and a dictionary that is designed for the Deaf target users at the school will be of far greater value in the learners' communication in both sign language and the written language. Certain components of the model can in fact also be implemented by users other than the original target users, so that it may also be of use to the broader Deaf community.This article investigates the typical equivalent relations in bilingual dictionaries and on that basis the core of the article makes suggestions about how the lexicographer could treat equivalent relations between sign language and Afrikaans in the proposed dictionary.